Improving the Spatial Ability of Distance Learning Students on the Material of Three-Dimensional Shapes through Mobile Learning Applications Based on Augmented Reality - Anam, Khaerul; Wiradharma, Gunawan; Prasetyo, Mario Aditya; Suko, Imelda Paulina (Universitas Muhammadiyah Mataram, 2023)
This research develops a mobile learning application that produces a feasible and attractive product to be used as a learning resource. Then, the product was tested quantitatively on users to determine the product's readiness and its relationship to increasing the user's spatial abilities. This research is a continuing research that has been carried out previously regarding the development of ABRAR (Application of three-dimensional shapes with Augmented Reality) application (Anam et al., 2022). The product has been validated by content and media experts and has received positive feedback from student users. Data was collected in Nusa Tenggara: Regional Offices of UT Mataram and UT Kupang, involving 3.098 Elementary Education Study Program students. The sample size consisted of 310 respondents, determined using the Lemeshow formula. The product produced from this research is an augmented reality-based mobile learning application that serves as a learning resource. The results of the mobile learning media trial developed were interpreted as very positive. It shows that using mobile learning in geometry subjects provides a positive response and increases motivation in the learning process. In addition, the implementation of mobile learning in spatial ability has shown a 30% improvement in imagining the position of three-dimensional shapes. It indicates that mobile learning has influenced the respondents' spatial ability. Respondents can visualize three-dimensional shapes from a certain point of view by utilizing augmented reality (AR) technology. Furthermore, based on the feasibility test results, the resulting mobile learning meets the criteria of being excellent and feasible to use as a geometry learning medium. The result of the research is mobile learning application so that it can be applied for distance education with requirements has an Android application system and easy to connect the internet. Thus, the ABRAR application can support learning anytime and anywhere, improve understanding of the material, and improve students' spatial abilities.